CONTENT ANALYSIS OF THE THIRD-YEAR INTERMEDIATE MATHEMATICS BOOK BASED ON THINKING KEYS - Dafaf Akram Abbas (Scholars Digest Publishing, 2025)
The current research aims to identify (analyzing the content of the mathematics book for the third intermediate grade according to the keys to thinking) To achieve the goal of the research, the researcher chose the descriptive approach in this research, and the method of content analysis was chosen because it is appropriate to achieve the goal of the research. The research population included the content of the mathematics book for the third intermediate grade, and the researcher excluded (the introduction, the index, and the questions at the end of the chapters), and thus the pages subject to analysis became ( 136) page. The researcher prepared the analysis tool for analyzing the content of the mathematics book for the third intermediate grade according to the thinking keys, which amounted to (20) keys after reviewing the educational literature and previous studies. For the purpose of ensuring the validity of the tool, it was presented to some experts and specialists in teaching methods, in order to express their opinions and observations. In it, the content of the mathematics book for the third intermediate grade was analyzed. To ensure the stability of the analysis, the researcher used the analysis method with the help of other analysts and using the Holsti equation. The reliability coefficient between the researcher and the first analyst reached (0.92), and between the researcher and the second analyst (0.94), and between the first and second analysts (0.96). The researcher analyzed again with a time difference of (fifteen days). It reached (96), and the idea and topic were used as units of analysis because they were appropriate to the goal of the research and the nature of the analyzed content. The analysis was done according to fixed principles and steps. The researcher extracted the results using frequencies and percentages of the thinking keys. In light of the research results, the researcher recommended: the need to use mathematics books according to the keys to thinking, and the need for those in charge to develop guidance programs that help develop thinking among learners, especially the keys to thinking. The researcher also included some suggestions, including: conducting a similar study in the middle school stage in mathematics, and conducting an evaluation study of mathematics books from the point of view of teachers and supervisors regarding the keys to thinking in those books.
Keywords: content analysis, thinking keys.